2013
DOI: 10.9721/kjfst.2013.45.3.356
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Inhibitory Effect of Aster scaber Thunb. Extract on Adipocyte Differentiation in 3T3-L1 Cells

Abstract: Clinical and preclinical trials of involving drugs with anti-obesity effects have focused on screening for herbal medicines suspected to have anti-obesity activities. In this study, an extract of Aster scaver Thunb., which was prepared in 80% methanol (ASE), was assessed for its total phenol content, total flavonoid content, antioxidant activity ability to scavenge the α-α-diphenyl-β-picrylhydrazyl, 2,2'-azino-bis-[3-ethylbenzthiazoline]-6-sulfonic acid radical, and anti-adipogenic effects. The anti-adipogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Previous studies have reported that the anti-adipogenic activities of Rumex crispus L. and Aster scaber Thunb. were associated with downregulated mRNA expression levels of transcription factors such as C/ EBP and PPAR families (31,32). Thus, based on the results, it was possible to conclude that 3T3-L1 adipogenesis was inhibited by WE and ME treatments through suppression of transcriptional factors including C/EBPβ, PPARγ, and C/EBPα levels.…”
Section: Resultsmentioning
confidence: 77%
“…Previous studies have reported that the anti-adipogenic activities of Rumex crispus L. and Aster scaber Thunb. were associated with downregulated mRNA expression levels of transcription factors such as C/ EBP and PPAR families (31,32). Thus, based on the results, it was possible to conclude that 3T3-L1 adipogenesis was inhibited by WE and ME treatments through suppression of transcriptional factors including C/EBPβ, PPARγ, and C/EBPα levels.…”
Section: Resultsmentioning
confidence: 77%
“…Furthermore, fisetin treatments led to inhibition of adipocytes-specific gene expression, including FAS and LPL. Anti-adipogenic activities of extracts from the natural materials Rumex crispus L. (a perennial flowering plant in the family Polygonaceae) and Aster scaber Thunb (a perennial herb of the Compositae family) were reportedly associated with inhibited mRNA expression levels of the transcription factors C/EBPs and PPARγ (27,28). Regulation of adipogenic transcriptional factors and adipocyte-specific genes reportedly plays an important role for inhibition of lipid accumulation (29,30).…”
Section: Resultsmentioning
confidence: 99%
“…A study has reported varying levels of anti-oxidant profiles in blanched, pan-fired and microwaved AS extract (Kim et al, 2014). AS ethanol extract has been reported to possess the anti-oxidant activity by reducing DPPH and antiadipogenic activity by suppressing the preadipocyte conversion in 3T3L1 cells (Choi et al, 2013). Hydrogen peroxide induced cell death in brain neuroblastoma SK-N-SH cells was also reported to be reversed by AS extract (Chung et al, 2016).…”
Section: Discussionmentioning
confidence: 98%